Meet the Other and (Re)define the Self : Africans in China and Chinese Imaginings of Race, Nation, and World Order - (:unkn) unknown (My University, 2024)
This dissertation is about Chinese perceptions of, discourses on, and interactions with Africans in China and what these tell us about how the Chinese imagine themselves and their place in the world. It unfolds in three parts. FIrst, I trace Chinese racial discourses for the turn of the 20th century to our contemporary time and show the many continuities and discontinuities across over a century. I highlight the convergence of race and nation and the role ''the West'' plays in the Chinese construction of their self-images.The second part focuses on the different and at times conflicting ways of perceiving and treating the out-group, and of defining what it means to be ''Chinese''. These differences and conflicts are expressions of deeper social dynamics and cleavages in the Chinese society. I examine these conflicting voices, their mutual interactions, as well as their perceptions of and interactions with the Chinese state. The thrid part situates day-to-day African-Chinese interactions in the broader context of China's diplomatic strategies and China-Africa economic relations. I demonstrate how seemingly abstract diplomatic rhetoric of China-Africa friendship plays out in African students' daily lives, and how national, local and personal strategies intermingle in the scene of China-Africa economic cooperation. I look at the many paradoxes and contradictions in Chinese perceptions of the Self and the Others, reveal the possible imperialist ambitions underneath China's quest for a new identity, and question possible altenative ways of self-imaginig.
Keywords: African Research